190 - THE SYSTEMATIZATION OF NURSING CARE (SAE): A REFLECTIVE ANALYSIS (Fiep Bulletin - online, 2011)
This article presents a reflection on the Systematization of Nursing Care (SAE) in Brazil in the last decade through a literature review of contextual analysis, performed using the material in the database of the Virtual Health Library (VHL), with redemption of full texts in English with the descriptors of systematization of nursing care and nursing process. The first institutions to adopt the SAE as a model for nursing were cardiology hospitals in the Southeast and some university hospitals in southern Brazil, and various other hospital experiences that started in a different way the deployment process. In 2002, the board of nursing affirmed its law as necessary to incorporate the SAE by the working class of nursing. On reflection we raise the following questions: How should this embodiment of the nursing process in practice everyday? Where should from the change initiative? Who can help this way? Although there are many studies in the SAE and records of implementation, which is observed is that there is still much doubt in the process of implementation in institutions of some regions of Brazil, and there is a dichotomy between service and professional education centers, revealing so real obstacles in implementing this model of nursing work. The SAE has developed in some regions of Brazil still by hand despite several successful experiences in implementing the NCS, however there is still a large space to be conquered and added to by nurses to assist in the implementation of a new methodology of work.
Keywords: systematization of nursing care; nursing care; nursing process